The Influence of Tiktok Social Media on the @kursusarab Account as an Arabic Language Learning Medium - Bunga Putri Rahmadani; Ady Muh. Zainul Mustofa; Anwar Sanusi; Neldi Herianto (Kilmatuna: Journal Of Arabic Education, 2026)
This study aims to analyze the influence of TikTok social media on the @kursusarab account as an Arabic language learning medium on students' learning interest at Al-Falah Islamic High School in Jambi City. The background of this study is the initial findings that indicate a lack of attention and interest in learning students in Arabic language learning. This study uses a quantitative method with a One Group Pretest Postest Design. The subjects of the study were eleventh grade students. Data were collected through pretest and posttest to measure students' interest before and after the application of TikTok social media on the @kursusarab account in the learning process. The research instrument used was a questionnaire statement test. The results showed a significant increase in students' learning interest after the use of TikTok social media on the @kursusarab account with an average pretest value of 56.40 increasing to 69.80 in the posttest. The paired TTest test showed a significance value of 0.001 (P <0.05), which indicates that TikTok social media on the @kursusarab account has a positive effect on students' learning interest. The results of this study are expected to provide a positive contribution in the development of more effective and interactive Arabic language learning methods at the secondary school level, as well as provide insight into the use of TikTok social media to increase students' interest in learning.